Soil Moisture Content, Yield and Water-use Efficiency of Cotton in Relation to in-situ Moisture Conservation Practices and Organic Manures under Rainfed Conditions - Hulihalli, U K; Patil, V C (Annals of Arid Zone, 2016)
Effect of in-situ moisture conservation practices and organic manures on soil moisture content, yield and water-use efficiency of cotton was studied at Agriculture Research Station, Annigeri, for two years. The compartment bunding (CB), broad furrow and ridge (BFR), and tied ridges furrows (TRF) resulted in significantly higher cotton yield as compared to flat bed (FB) and contour cultivation (CC). The water-use efficiency and net returns were also higher with CB, BFR and TRF. The yield was higher with farmyard manure (5 t ha-1) and poultry manure (5 t ha-1) as compared to cotton stalk incorporation @ 5 t ha-1. Key words: Compartment bunding, broad furrow and ridge, tied ridges and furrows, flat bed contour cultivation, in-situ moisture conservation, organic manures.